One-Pot Access to 2-Aryl-3-(arylmethyl)chromones - Chang, Meng-Yang; Chen, Kuan-Ting; Tsai, Yu-Lin; Chen, Han-Yu (Synthesis, 2020)
Sodium hydroxide controlled intermolecular double aldol condensation of o-hydroxyacetophenones with 2 equivalents of arylaldehydes provides 2-aryl-3-(arylmethyl)chromones (a chimera of flavone and homoisoflavanone) in MeOH at 50 °C under mild conditions. The uses of various bases and solvents are investigated for one-pot facile and efficient transformation. A plausible mechanism is proposed.
Keywords: aldol condensation; o-hydroxyacetophenones; arylaldehydes; chromones; homoisoflavanone; benzopyran-4-one